Effectiveness of Pictures in Enhancing ESL Students’ Short Story writing Ability (Voice: A Biannual & Bilingual Journal, 2023)
The integration of pictures into story teaching offers a dynamic approach that caters to various learning styles, fosters deeper understanding, and makes the learning experience more enjoyable. This quantitative pre-experimental research was conducted to investigate the impact of visuals on enhancing short story writing skill among secondary level ESL (English as a Second Language) students. Data was derived from a sample of thirty students selected purposively for the study. The research incorporated pre-tests, progressive tests, and post-tests as data collection techniques. The outcomes of these tests were subsequently compared and analyzed to assess the influence of visuals on short story development. The analysis of the data revealed that pictures were indeed effective in teaching short story composition to secondary level students. Therefore, utilizing visuals as an instructional tool for teaching short story writing is recommended for secondary level ESL students.